The Dead Brotherâ€™s Ballad as a Balkan Shared Place of Memory - Kulavkova, Katica (European Scientific Journal, ESJ, 2021)
There is a ballad saved in the folklore and oral literary tradition of several Balkan peoples and their collective memory under different names, but with the same proto narrative: â€œThe Dead Brotherâ€™s Songâ€ (Greek), â€œThe Return of the Dead Brotherâ€ (Macedonian), â€œBrother and Sisterâ€ (Serbian, Montenegrin, Bosnian), â€œLazar and Petkanaâ€ (Bulgarian), â€œConstantin and DoruntinÃ«â€ (Albanian), and â€œVoikaâ€ (Romanian). Appearing in several linguistic and stylistic variants, this ballad can be considered as an illustrative shared place of collective Balkan memory. Saved both as a local (national), and regional (transnational) cultural heritage, Ð¢he Dead Brotherâ€™s Ballad contains the most significant aspects of the Balkan cultural paradigm: mythical, mystical, folkloric, religious, ethical, and historical ones. The interpretation of this ballad in the mythopoetic context demystifies the Balkan identity prejudices and the misinterpretation of the shared cultural heritage. Methodologically, the present interpretation of the Balkan ballad is syncretic, combining diverse theoretical and interpretative tools from mythology, theory of literature, culturology and post-postcolonial criticism. Instead of giving an ultimate conclusion, this paper deconstructs the dominant interpretative strategies of the Balkan spiritual and historical heritage in the last two centuries (adoptive, contestable, convertible, competitive) showing that they all actualise the conservative principles of cultural hegemony on the Balkans. Having a scientific consensus for the transnational aspects of the Balkan cultural heritage might be a starting point for a new, empathetic strategy of their perception.